140k views
14 votes
Please answer the questions

Please answer the questions-example-1
Please answer the questions-example-1
Please answer the questions-example-2
User PaulF
by
5.2k points

1 Answer

5 votes

Answer:

1/18

Explanation:


( {2}^( - 3) * {16}^{ (1)/(2) } ) / ( {81}^{ (3)/(4) } * {27}^{ - (1)/(3) } ) \\ \\ =( {2}^( - 3) * {2}^{ (4 * 1)/(2) } ) / ( {3}^{ (4 * 3)/(4) } * {3}^{ - (3 * 1)/(3) } ) \\ \\=( {2}^( - 3) * {2}^( 2) ) / ( {3}^( 3 ) * {3}^( - 1 ) ) \\ \\=( {2}^( - 3 + 2) ) / ( {3}^( 3 - 1 ) ) \\ \\ = {2}^( - 1) / {3}^(2) \\ \\ = (1)/(2) * (1)/(9) \\ \\ = (1)/(18)

User Cateyes
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.